Disparities in Screening Mammography Services by Race/Ethnicity and Health Insurance - Rauscher, Garth H. (Mary Ann Liebert, Inc., 2012)
BACKGROUND: Black and Hispanic women are diagnosed at a later stage of breast cancer than white women. Differential access to specialists, diffusion of technology, and affiliation with an academic medical center may be related to this stage disparity. METHODS: We analyzed data from a mammography facility survey for the metropolitan region of Chicago, Illinois, to assess in part whether quality breast imaging services were equally accessed by non-Hispanic white, non-Hispanic black, and Hispanic women and by women with and without private insurance. Of 49 screening facilities within the city of Chicago, 43 facilities completed the survey, and 40 facilities representing about 149,000 mammograms, including all major academic facilities, provided data on patient race/ethnicity. RESULTS: Among women receiving mammograms at the facilities we studied, white women were more likely than black or Hispanic women to have mammograms at academic facilities, at facilities that relied exclusively on breast imaging specialists to read mammograms, and at facilities where digital mammography was available (p<0.001). Women with private insurance were similarly more likely than women without private insurance to have mammograms at facilities with these characteristics (p<0.001). CONCLUSIONS: Black and Hispanic women and women without private insurance are more likely than white women and women with private insurance to obtain mammography screening at facilities with less favorable characteristics. A disparity in use of high-quality mammography may be contributing to disparities in breast cancer mortality.